Thyroid autoimmunity and autoimmune thyroid disease in Malaysian girls with Turner syndrome: an understudied population - Lee, Yee L; Zaini, Azriyanti A; Idris, Arini N; Abdullah, Raja A; Wong, Jeanne SL; Hong, Joyce SS; Hussain, Suhaimi; Lim, Poi G; Lim, Song H; Nor, Noor SM; Wu, Loo L; Jalaludin, Muhammad Y (Wiley, 2023)
Aims: Knowledge on the spectrum of thyroid disorders amongst Turner syndrome (TS) patients in Southeast Asia is limited. This study aimed to evaluate the prevalence of thyroid autoimmunity, the spectrum of autoimmune thyroid disease and association with age and karyotype amongst Malaysian TS girls.